Secondary analyses to test the impact on inequalities and uptake of the schools-based human papillomavirus (HPV) vaccination programme by stage of implementation of a new consent policy in the south-west of England. Issue 7 (7th July 2021) - Fisher, Harriet; Evans, Karen; Reynolds, Rosy; Yates, Julie; Roderick, Marion; Ferrie, Jo; Macleod, John; Hickman, Matthew; Audrey, Suzanne
Abstract : Objectives: To test the impact on inequalities and uptake of the schools-based human papillomavirus (HPV) vaccination programme by stage of implementation of a new policy providing additional opportunities to consent. Setting: Two local authorities in the south-west of England. Participants: Young women (n=7129) routinely eligible for HPV vaccination aged 12–13 years during the intervention period (2017/2018 to 2018/2019 programme years). Interventions: Local policy change that included additional opportunities to provide consent (parental verbal consent and adolescent self-consent). Outcomes: Secondary analyses of cross-sectional intervention data were undertaken to examine uptake by: (1) receipt of parental written consent forms and; (2) percentage of unvaccinated young women by stage of implementation. Results: During the intervention period, 6341 (89.0%) eligible young women initiated the HPV vaccination series. Parental written consent forms were less likely to be returned where young women attended alternative education provider settings (p<0.001), belonged to non-white British ethnic groups (p<0.01) or more deprived quintiles (p<0.001). Implementation of parental verbal consent and adolescent self-consent reduced the percentage of unvaccinated young women from 21.3% to 16.5% (risk difference: 4.8%). The effect was greater for young women belonging to the most deprived compared with the least deprived quintile (risk difference: 7.4% vs 2.3%, p<0.001), and for young women classified as Unknown ethnic category compared with white British young women (6.7% vs 4.2%, p<0.001). No difference was found for non-white British young women (5.4%, p<0.21). Conclusions: Local policy change to consent procedures that allowed parents to consent verbally and adolescents to self-consent overcame some of the barriers to vaccination of young women belonging to families less likely to respond to paper-based methods of gaining consent and at greater risk of developing cervical cancer. Trial registration number: 49 086 105.